EFEKTIVITAS DAN EFISIENSI PEMBELAJARAN BERBASIS BLENDED LEARNING DI MADRASAH TSANAWIYAH NEGERI MODEL PALU - Ramang (Paedagogia: Jurnal Pendidikan, 2018)
The learning process in the Palu State Islamic Education Madrasah has run as it should, although in terms of strategies, methods, and learning media used varies according to the conditions, both the material and the condition of the students, and the ability of the teacher itself is different from one another. Blended learning based learning at the Palu Model State Islamic Education Madrasah is considered effective and efficient because teachers are not preoccupied with making material designs, simply accessing the internet is needed including practice in the form of videos so that it will facilitate teachers, both in terms of time, effort and cost. The challenge of blended learning is that teachers are required to be more creative and able to use internet networks. While the opportunity is the Madrasah Tsanawiyah Negeri Model Palu already equipped with network facilities and infrastructure that can support blended learning.